Expression of vascular Notch ligands Delta-like 4 and Jagged-1 in glioblastoma. - Jubb, A; Browning, L; Campo, L; Turley, H; Steers, G; Thurston, G; Harris, A; Ansorge, O (2012)
AIMS: The coordinated expression of the Notch ligands Delta-like 4 (Dll4) and Jagged (Jag)1 is believed to define appropriate endothelial sensitivity to vascular endothelial growth factor (VEGF). Preclinical data suggest that Dll4-Notch signalling may confer resistance to anti-VEGF therapy with bevacizumab, and Jag1 may antagonize Dll4-Notch. The aims of this study were to characterize the expression of Dll4 and Jag1 in primary glioblastomas. METHODS AND RESULTS: Immunohistochemistry was performed on 40 glioblastomas and normal brain using validated antibodies against Dll4 and Jag1. In-situ hybridization for Dll4 was performed on serial sections and compared with protein expression. Dll4 expression was localized to the cytoplasm and membrane of endothelial cells in all glioblastomas; it was weak or absent in normal brain. Jag1 expression was observed in the cytoplasm and membrane of glomeruloid and non-glomeruloid endothelial cells from 76% and 67% of glioblastomas, respectively. However, endothelial Jag1 expression was less intense and less prevalent than Dll4. There was no association between Dll4 and Jag1 expression. CONCLUSIONS: In summary, Dll4 and Jag1 are expressed in glioblastoma vasculature. These data may define subsets of glioblastoma that might be sensitive (Dll4(+) /Jag1(+) ) or resistant (Dll4(+) /Jag1(-) ) to bevacizumab. Our data also suggest that anti-Dll4 therapy should be evaluated experimentally in glioblastoma.